PENGARUH KUALITAS LAYANAN DAN KEUNGGULAN PRODUK TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA PADA KOMUNIKASI WORDS OF MOUTH (Studi pada PD BPR BKK Demak Cabang Sayung, Kab.Demak) - Dyah Kusumawati; Abdul Syakur (Jurnal Administrasi Bisnis, 2016)
Intense competition among banking institutions in terms of marketing products and services to customers in creating a communication satisfaction will influence the words of mouth . Plus builds consumer confidence in yourself is relatively more difficult than just selling products only. Therefore creating a satisfaction to the customers is an absolute thing to do because it can provide the benefits of customer satisfaction for banks . This study aims to analyze whether the quality of service and product excellence affects customer satisfaction and how it impacts on words of mouth communication. The method used is a quantitative method to research the type of survey and questionnaire . Sampling was done by purposive sampling method . The results of the questionnaire were calculated using path analysis  with the help of SPSS software . The results show the quality of service affects customer satisfaction 0.373 , product excellence 0.346 and affect customer satisfaction for both together can affect customer satisfaction by 0.154 . WOM affects service quality by 0.101 , the superiority of the product affects WOM 0.092 and both together can affect WOM by 0.166 . The impact of satisfaction with the emergence of communication words of mouth is positive at 0.446 . The calculation of the indirect effect of variables X1 and X2 to Y2 through Y1 is greater than the calculation of the direct effect , this means that the customer satisfaction as a mediating variable of influence of quality of service and product excellence to positively impact WOM and proven.